Development and bioassessment of high nutria-omega 5 cookies through animal modeling - Iqbal, Nida; Shabbir, Muhammad Asim; Khan, Moazzam Rafiq; Faisal, Muhammad Naeem (Frontiers in Nutrition, 2023)
Fruit processing in food industries produces a variety of waste byproducts which can be modified to develop various functional foods and other commodities. In this study, leftover agro-waste products of pomegranate juice were used to make pomegranate seed oil (PSO), and sunflower oilseed cake was used to produce sunflower meal protein concentrate (SMPC), which was then collectively utilized to make High Nutria Omega 5 (HNO5) cookies. Pomegranate seed oil was evaluated in the study using a variety of laboratory analytical procedures. Both of these extracted components were utilized in varied ratios to develop High Nutria Omega 5 (HNO5) cookie products that further underwent sensory, physicochemical, storage, and proximate evaluations. Over a 45-day efficacy period, the treatments were observed for various serum analyses. As compared to the control feed, the findings of the renal and liver functional tests also indicated a favorable effect on ALT, AST, ALP, serum urea, creatinine, albumin, globulins, total proteins, and A/G ratio. The results revealed that PSO and SMPC cookies containing 15% PSO and 15% SMPC exhibited stability in numerous physicochemical and sensory assessments. The punicic acid in HNO5 cookies significantly reduced the effects of starvation in rats and progressively improved several metabolic processes and overall health profiles. Similarly, SMPC in cookies improved body weight and overall health. The findings revealed that cookies made of PSO and SMPC can be served as a functional food provided proper concentrations of these byproducts can be replaced with vegetable shortening and flour in tackling malnutrition.